APB Rembau e-bulletin 14th edition October 18, 2024 / UiTM, Academy of Language Studies - Academy of Language Studies, UiTM Negeri Sembilan (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
No portion of this bulletin may be copied or otherwise transmitted in any manner, whether electronically or mechanically, including by photocopying, recording, or information storing and retrieval systems without the publisher's permission. This e-bulletin is only intended to provide general information for educational purposes. The information on this e-bulletin represents the author's opinions, and the publisher disclaims responsibility for the reliability and validity of the source. The publisher also disclaims all liability for errors and any loss or harm readers may incur due to using the information and/or resources in this e-bulletin.